2021
DOI: 10.4236/ojd.2021.103008
|View full text |Cite
|
Sign up to set email alerts
|

The Patient Health Questionnaire-9 among First-Trimester Pregnant Women in Japan: Factor Structure and Measurement and Structural Invariance between Nulliparas and Multiparas and across Perinatal Measurement Time Points

Abstract: Background: Depression is frequently seen among pregnant women. The PHQ-9 is a diagnostic criteria-based screening instrument. Objective: The objective is to identify the factor structure of the Patient Health Questionnaire-9 (PHQ-9) and to confirm its measurement and structural invariance regarding parity and observation time, as well as to examine reliability by calculating omega indices in a population of pregnant Japanese women. Methods: The PHQ-9 was distributed to 382 pregnant women with a gestational ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The second factor consists of loss of interest, depressed mood, self-blame, concentration difficulty, psychomotor symptom, and suicidality items. Measurement invariance has been confirmed Wakamatsu et al [ 43 ].…”
Section: Methodsmentioning
confidence: 69%
“…The second factor consists of loss of interest, depressed mood, self-blame, concentration difficulty, psychomotor symptom, and suicidality items. Measurement invariance has been confirmed Wakamatsu et al [ 43 ].…”
Section: Methodsmentioning
confidence: 69%
“…Two studies involving Peruvian pregnant women agreed on indicating the same two-factor solution with the same items assigned to each scale (Smith et al 2022a , b ; Zhong et al 2014 ). Similarly, a Japanese study found a two-factor model but with different assignments of items to scales (Wakamatsu et al 2021 ). Further two studies involving Ethiopian versus Ivorian and Ghanaian pregnant women suggested a one-factor structure (Barthel et al 2015 ; Woldetensay et al 2018 ).…”
Section: Discussionmentioning
confidence: 95%
“…This was a secondary analysis of our previously reported epidemiological dataset [26][27][28][29]. Approximately 1500 pregnant women in the period of 10 to 13 weeks' gestational age were recruited at the antenatal clinic of one general hospital and five private clinics located in Tokyo, Chiba, Ibaraki, and Kagoshima Prefectures in Japan.…”
Section: Study Procedures and Participantsmentioning
confidence: 99%
“…The psychometric properties' validity and reliability of the Japanese version of PHQ-9 were reported [31,32]. We already reported a result of a factor analysis of the PHQ-9 items among current expectant women that yielded two subscales, somatic and non-somatic [26]. The somatic subscale included the items 'sleep', 'fatigue', and 'appetite', whereas the nonsomatic subscale included the items 'loss of interest', 'depressed mood', 'self-esteem', 'poor concentration', 'psychomotor', and 'suicidality'.…”
Section: Measurementsmentioning
confidence: 99%